The Chloraea from Lima, a little-known species but described several times - Trujillo, Delsy; Paredes-Burneo, Diego (Lankesteriana: International Journal on Orchidology, 2020)
During the botanical expedition carried out in Peru by Ruiz and Pavón, later by Raimondi’s explorations and finally by Weberbauer’s, specimens of a Chloraea species were collected in localities around Lima and used to describe Chloraea pavonii, C. undulata and C. peruviana. In this study we reviewed original materials, protologues, drawings, additional herbarium specimens and living material to clarify the taxonomic status of C. pavonii. A description, illustration, photographs, and distribution of the species are provided. We also point out the morphological features that distinguish C. pavonii from C. densipapillosa and C. septentrionalis. Lectotypes for C. undulata and C. peruviana are here designated. Key Words: Chloraea, Lima, Peru, lectotypification, lomas ecosystem